NAVIGATING THE DIGITAL ABYSS: EXPLORING THE NEXUS BETWEEN LONELINESS, AGGRESSIVE BEHAVIOR, AND SMARTPHONE ADDICTION AMONG COLLEGE STUDENTS - Lestari, Lesi; Yandri, Hengki; Sujadi, Eko (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2024)
Smartphone addiction has become a growing concern, potentially linked to negative outcomes in adolescents. This study aimed to analyze the influence of loneliness and aggressive behavior on smartphone habits among teenagers. Employing a quantitative approach, the research utilized a correlational design with a sample of 87 students. The study instruments included validated and reliable scales for measuring loneliness, aggressive behavior, and smartphone addiction. Data analysis involved multiple aggression analysis. The results revealed a significant association between both loneliness and aggressive behavior with smartphone use. This suggests that adolescents experiencing loneliness or exhibiting aggressive tendencies might engage in more frequent or problematic smartphone use. Building upon these findings, future research could delve deeper into the potential of digital education and media literacy programs to support healthy smartphone habits and reduce excessive use among adolescents. Additionally, investigating the impact of such programs on the development of guidance and counseling services for university students could be valuable.